Mesectodermal leiomyoma of the ciliary body: Two Vietnamese case reports - Chu Van Nguyen; Huyen Thi Phung; Quang Tien Nguyen; Tuan Anh Hoang (Elsevier, 2020)
Mesectodermal leiomyoma of the ciliary body is exceptionally a rare intraocular tumor and apparently benign tumor is considered embryologically originating from the neural crest (ectoderm). Clinically, it is challenging identifying the mesectodermal leiomyoma and the most important differential diagnosis is uveal melanoma. We reported two females who presented the enlarged mesectodermal leiomyomas of the ciliary body of the right eye. The first patient was made newly diagnosed and the remaining one was locally recurred after 10-year the first surgeon. Histopathological and immunohistochemical findings demonstrated the mesectodermal leiomyoma. Early diagnosis and timely radical surgery is necessary to avoid ocular complications and local recurrence.